Nineteeth-century sealing operations in the South Shetland Islands: Log of the Sarah W Hunt, 1887-88 - Salerno, Melisa Anabella; Cruz, María Jimena
Table describing sealing operations conducted by the American schooner Sarah W. Hunt of Stonington in the South Shetland Islands, during its 1887-88 voyage (Capt. James W. Budington). Based on information provided by the manuscript of the Log of the Sarah W. Hunt (Oct 1887 – Dec 1888). Mystic Seaport Museum, G. W. Blunt White Library, Roll MR 2. Table created for discussing the diversity of nineteenth-century sealings strategies in Antarctica and its potential archaeological footprint. Fil: Salerno, Melisa Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina Fil: Cruz, María Jimena. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina